Developing PAIKEM-Oriented Blended Learning Media for Improving Students’ Academic Achievement - Hendra Helwaun; Vigo Yano Sahertian; Meilany Angkota Mony; Christiani Monica Moniharapon; Novita Loma Sahertian (Jurnal Pendidikan Agama Kristen (JUPAK), 2026)
This study aims to examine the development and implementation of PAIKEM-oriented blended learning media as an instructional innovation to improve students’ academic achievement. Rapid technological advancement in the digital era has significantly transformed educational paradigms, making the integration of information and communication technology an essential requirement in 21st-century learning. In response to this shift, the development of effective and engaging learning media has become increasingly important, particularly in religious education contexts.Christian Religious Education not only provides students with opportunities to construct knowledge and deepen conceptual understanding, but also encourages the internalization and application of values reflected in students’ attitudes and communication. The adoption of a PAIKEM (Active, Innovative, Creative, Effective, and Joyful Learning) approach within a blended learning environment is considered a strategic alternative to promote student engagement and enhance learning outcomes, especially during the pandemic period.The findings indicate that the implementation of PAIKEM-oriented blended learning media at SD Inpres Namano enabled students to participate in diverse learning activities that fostered understanding, skills development, and active learning. Teachers were required to utilize various learning resources and instructional tools, including the surrounding environment, to create an active, innovative, engaging, and enjoyable learning atmosphere. Overall, the use of interactive multimedia-based blended learning media grounded in the PAIKEM approach proved to be an effective alternative for supporting Christian Religious Education instruction and improving students’ academic achievement.